Key findings from the UKCCMP cohort of 877 patients with haematological malignancy and COVID‐19: disease control as an important factor relative to recent chemotherapy or anti‐CD20 therapy. (10th November 2021) - Booth, Stephen; Curley, Helen M.; Varnai, Csilla; Arnold, Roland; Lee, Lennard Y. W.; Campton, Naomi A.; Cook, Gordon; Purshouse, Karin; Aries, James; Innes, Andrew; Cook, Lucy B.; Tomkins, Oliver; et al.
Summary: Patients with haematological malignancies have a high risk of severe infection and death from SARS‐CoV‐2. In this prospective observational study, we investigated the impact of cancer type, disease activity, and treatment in 877 unvaccinated UK patients with SARS‐CoV‐2 infection and active haematological cancer. The primary end‐point was all‐cause mortality. In a multivariate analysis adjusted for age, sex and comorbidities, the highest mortality was in patients with acute leukaemia [odds ratio (OR) = 1·73, 95% confidence interval (CI) 1·1–2·72, P = 0·017] and myeloma (OR 1·3, 95% CI 0·96–1·76, P = 0·08). Having uncontrolled cancer (newly diagnosed awaiting treatment as well as relapsed or progressive disease) was associated with increased mortality risk (OR = 2·45, 95% CI 1·09–5·5, P = 0·03), as was receiving second or beyond line of treatment (OR = 1·7, 95% CI 1·08–2·67, P = 0·023). We found no association between recent cytotoxic chemotherapy or anti‐CD19/anti‐CD20 treatment and increased risk of death within the limitations of the cohort size. Therefore, disease control is an important factor predicting mortality in the context of SARS‐CoV‐2 infection alongside the possible risks of therapies such as cytotoxic treatment or anti‐CD19/anti‐CD20 treatments.